Information Seeking Behavior through Crowd sourcing among Students in Selected Arts & Science Colleges at Salem District affiliated to Periyar University - Poongodi, K.; Shanthi, J. (Qualitative and Quantitative Methods in Libraries; Vol 6 No 1 (2017): March 2017 Issue, 2019)
In this work we use the theory of crowd sources as a lens to compare and dissimilarity a number of quality tools currently in use by the institutions for crowd engagement purposes. We provide to practitioner community with a convenient and useful resource in table form outlining some of the differing potentialities of crowd quality engaging tools. The study was based on Ellis Model to identify the crowd quality dimensions in seven aspects like starting, chaining, browsing, Differentiating, Monitoring, Extracting, Verifying & Ending to improve the existing systems. This system of resources also highlight on analyzing the students information seeking behavior in crowd resources. This is a study which is done on Students in Selected Arts & Science Colleges at Salem District affiliated to Periyar University, Salem to find out the effectiveness of quality dimensions in learning resource centre. Convenience sampling method is used for the study. The sample size was taken as 105 and it was analyzed by using simple percentage analysis and chi-square. The study founded that the students has a better quality dimension crowd resources in Monitoring and Extracting were provided up to the level of satisfying the seeking needs of information in crowd environment. If the environment is able to upgrade its process this study can get the top of the list in the LIS.